Digital Transformation Of MSME Financial Recording Cash Flow Family Business - Sri Hatuti; Dwi Ekasari Harmadji (Universitas Islam Lamongan, 2022)
The purpose of research on digital transformation of MSMEs in financial records is to review MSME cash flows in family businesses and the contributing factors. The qualitative method of explanatory descriptive analysis for the validity of the data uses triangulation of sources and data. Triangulation process with 3 stages, first coding, second axial & selection coding, third conclusion. 14 informants to support the formulation of the problem causing difficulties in financial recording. The results show 7 factors that make it difficult for MSMEs to digitally record their finances. For micro-scale family businesses, digitization of financial records is still very simple. Suggestions for future researchers to provide direct assistance and training to MSMEs regarding digital financial records.